ChemInform Abstract: A New Improved Method for the Synthesis of 2, 4‐Diarylpyrimidines Starting from 2, 2, 2‐Trichloroethylideneacetophenones. Issue 1 (7th January 2014) - Guirado, Antonio; Alarcon, Enrique; Vicente, Yesica; Andreu, Raquel
Abstract A novel synthetic method for pyrimidine synthesis is demonstrated using the reaction of 2, 2, 2‐trichloroethylideneacetophenones with enamides.